Azobenzene-derived tris-β-diketonate lanthanide complexes: reversible trans-to-cis photoisomerization in solution and solid state. Issue 38 (23rd August 2016) - Lin, Li-Rong; Wang, Xuan; Wei, Gao-Ning; Tang, Hui-Hui; Zhang, Hui; Ma, Li-Hua
Abstract : Azobenzene-derived tris-β-diketonate lanthanide complexes were synthesized and they show good trans -to- cis photoisomerization behavior both in solution and in the solid state. Abstract : Novel azobenzene-derived β-diketonates (4, 4, 5, 5, 6, 6, 6-heptafluoro-1-azobenzene-1, 3-hexanedione (LA ), 4, 4, 5, 5, 6, 6, 6-heptafluoro-1-(4-dimethylamino)azobenzene-1, 3-hexanedione (LB )) were designed and their complexes with lanthanide cations (La 3+, Eu 3+, Gd 3+, Yb 3+ ) were prepared and characterized by 1 H NMR, FT-IR, and elemental analysis. Three of the complexes were crystallized successfully and identified by X-ray diffraction. It was significant to find thatLA showed remarkably reversible trans -to- cis isomerization properties, however, LB, bearing an electron donor compared withLA, slowed down the isomerization to an extent. The presence of Ln(iii ) enhanced the reversible trans -to- cis isomerization properties of bothLA andLB a little upon photoirradiation in organic solvents, and amazingly increased the fatigue resistance. In addition, the complexes doped in polymethyl methacrylate (PMMA) films produced a similar phenomenon as well as when in solution. Theoretical calculations based on time dependent density functional theory (TD-DFT) were performed for geometry optimization and to determine the excitation energies ofLA andLB to gain further insight into the electronic structure of the complexes, and the data were consistent with the experimental results. The excellent reversible photoisomerization properties of the newly designed Ln(iii ) complexes can offer important advantages that will help with the further study of these materials to reach their full potential in applications such as molecular switching devices.